Voices of Authority and Linguistic Autonomy in Niebla - Mary Lee Bretz (Studies in 20th & 21st Century Literature, 1987)
Miguel de Unamuno's works have often been studied as expressions of his philosophy or life experience. More recent literary theory has eschewed approaches that foreground the author, preferring to focus primarily on the text or the reader. Utilizing Mikhail Bakhtin's theory of the novel, this paper analyzes Niebla, one of Unamuno's most frequently studied works, to illustrate that new literary theories can enrich our reading of the text. Bakhtin argues that the novel is characterized by many voices or styles which the novelist welcomes and exploits. The novel should not be viewed as having a single style but as a dynamic interaction between a variety of incorporated languages. The authorial voice is only one among many and it is constantly challenged, muted, and reshaped as it enters into contact with other voices that are present in the text. "Authoritative discourse" is only one type of discourse that can be incorporated into the novel, especially a Bildungsroman. In the process of maturation, the character passes through a series of ideological phases, each of which is characterized by the interaction of the character's language and the language of a given authority. Unamuno's Niebla is essentially a Bildungsroman, in which Augusto Pérez progresses through a series of stages in an existentialist quest for self. These stages are accompanied by linguistic changes, as Augusto gradually sheds the voices of authority and acquires his own autonomous voice. The culmination of this process occurs in the famous scene where Augusto confronts Unamuno. The meeting of author and character is more than an expression of Unamuno's thirst for eternal life through literature; it is a dramatization of the nature of heteroglossia and a confirmation of the linguistic autonomy of the fictional character.
Keywords: Miguel de Unamuno; Spanish literature; philosophy; text; reader; Mikhail Bakhtin; Niebla; literary theory; voices; voice; authoritative discourse; discourse; Bildungsroman; existentialism; self; journey; quest for self; author; character; eternal life; heteroglossia; linguistic autonomy